STRATEGI PROGRAM INDEKS PEMBANGUNAN MANUSIA (IPM) DI DESA PAKUAON KECAMATAN SUKARESMI KABUPATEN CIANJUR - Muhammad Taufan Ashshiddiqi; Ichsan Firmansyah; Khairu Syifa Ahyani; Laila Febriyuni Eka Putri; Mochammad Fajar Maulana (Jurnal Inovasi Penelitian, 2021)
Based on data from the Central Statistics Agency (BPS) of West Java Province in 2020, the HDI of Cianjur Regency is in the last place. One of the efforts to overcome this inequality is to make programs as a human development strategy as carried out by Pakuon Village, Sukaresmi District, Cianjur Regency. The research problem encountered is the low quality of human resources in Pakuon Village seen from the 3 main indicators of the Human Development Index (HDI), namely based on health indicators, education level indicators and economic indicators. This study aims to identify and describe the strategy of the Human Development Index Program (IPM) in Pakuon Village. The method in this research uses a descriptive qualitative approach. The results of the study show that the HDI program in Pakuon Village has been running, but has not been optimal because it is constrained by internal and external problems.